Exploring the benefits to caregivers of a family-oriented pulmonary rehabilitation program - Figueiredo, Daniela (2018)
BACKGROUND: COPD is a highly incapacitating disease, particularly among older people, implying significant burden for family caregivers. Involving caregivers in comprehensive pulmonary rehabilitation programs might benefit their functional coping to care demands; however, there is no objective evidence to sustain such assumption. This study is a secondary analysis aiming to analyze the effects of a family-based pulmonary rehabilitation program on close family caregivers of older subjects with COPD. METHODS: This is a mixed-method study. Family caregivers were randomly assigned to family-based (experimental) or conventional (control) pulmonary rehabilitation. Caregivers from the family-based pulmonary rehabilitation (n = 20; 80.0% female; age 63.1 ± 9.5 y) attended the psychoeducational component together with their relatives. In the conventional pulmonary rehabilitation, caregivers did not participate (n = 19; 68.4% female; age 53.6 ± 11.3 y). Self-rated instruments (Family Crisis Oriented Personal Scales, Depression Anxiety and Stress Scales, and Carers' Assessment of Difficulties Index) and focus group interviews were used to assess the intervention. RESULTS: Caregivers from the family-based pulmonary rehabilitation had significantly greater improvements in overall family coping (P = .01), reframing (P = .01), seeking spiritual support (P = .01), and mobilizing to acquire help (P = .02). No significant differences were found for emotional state. Significant improvements in overall burden (P = .01), reactions to caregiving (P = .01), physical demands of caring (P = .044), and poor family support (P = .038) were observed, although there were no significant between-group differences. Qualitative data sustained the benefits of involving family caregivers in pulmonary rehabilitation. CONCLUSIONS: The findings provide valuable evidence to recommend the inclusion of COPD family caregivers in comprehensive pulmonary rehabilitation. Family-oriented pulmonary rehabilitation maximizes caregivers' adaptive coping and potentially prevents negative psychological outcomes; however, further research is needed.